Accuracy, precision and knee replacement: a cautionary tale. Issue 1 (January 2016) - Cobb, Justin
Abstract : Technological advances and increased surgical precision should have resulted in knee replacements that can be 'forgotten' by patients, but patients continue to be dissatisfied by the results of their knee replacement surgery. In this article the author gives his opinion on why this might be and highlights a new approach that he believes could revolutionise knee surgery.